Nutrition for marathon running - Koehler, K. (Marathon running: Physiology, psychology, nutrition and training aspects, 2016)
Marathon runners can uniquely benefit from nutritional strategies that support their training responses and/or maximize their performance during the actual race. Promising strategies during marathon training include the adequate provision of dietary energy, macronutrients (carbohydrates, protein), and selected micronutrients (e.g., iron) to meet the increased requirements of prolonged distance running. Nutritional and training approaches aimed at increasing fat oxidation rates or facilitating weight loss may be associated with negative effects and should therefore be conducted with care. During the actual marathon race, runners can benefit from carbohydrate loading strategies that serve to maximize pre-race muscle glycogen storage capacity. Consumption of carbohydrates, fluid, and sodium can prevent preemptive fatigue due to nutrient depletion, and caffeine supplementation can provide ergogenic effects during prolonged running. Because the responses to these nutritional interventions can vary substantially among individuals and require fine tuning depending on factors such as performance level, environmental conditions, designated running pace, propensity for gastrointestinal discomfort, and availability of aid stations during the race, marathon runners are highly encouraged to familiarize themselves with these strategies prior to utilizing them in a competitive setting.